2020
DOI: 10.1017/s0033291720002925
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of treatments for alcohol-related cognitive impairment: lessons from the past and gaps for future interventions

Abstract: Alcohol-related cognitive impairment (ARCI) is highly prevalent among patients with alcohol dependence. Although it negatively influences treatment outcome, this condition is underdiagnosed and undertreated. The aim of this systematic review is to investigate the existing evidence regarding both cognitive and pharmacological interventions for ARCI. We systematically reviewed PubMed, Scopus and Science direct databases up to May 2019 and followed the PRISMA guidelines. The quality of the studies was assessed us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 78 publications
(151 reference statements)
1
15
0
Order By: Relevance
“…Bates et al (2013) assert that neurocognitive impairments ranging from mild to severe are prevalent in most people with AUD but the de cits can be minimal, transient and even improve with sustained abstinence. A systematic review by Caballeria et al (2020) highlighted studies that have looked into the bene ts of what is called the component method which is a rehabilitative strategy of breaking down complex tasks into smaller and easier to navigate components and small improvements in visuospatial skills were noted after one month of abstaining from alcohol. However, evidence in earlier studies had already indicated that impairment in this domain improved rapidly with abstinence (Sullivan 2008, Rosenbloom et al 2000.…”
Section: Abstinencementioning
confidence: 99%
“…Bates et al (2013) assert that neurocognitive impairments ranging from mild to severe are prevalent in most people with AUD but the de cits can be minimal, transient and even improve with sustained abstinence. A systematic review by Caballeria et al (2020) highlighted studies that have looked into the bene ts of what is called the component method which is a rehabilitative strategy of breaking down complex tasks into smaller and easier to navigate components and small improvements in visuospatial skills were noted after one month of abstaining from alcohol. However, evidence in earlier studies had already indicated that impairment in this domain improved rapidly with abstinence (Sullivan 2008, Rosenbloom et al 2000.…”
Section: Abstinencementioning
confidence: 99%
“…Moreover, previous reports revealed neuronal apoptosis when an individual was exposed to chronic alcohol abuse. 7,29,30 Therefore, it can be postulated that this desirable amelioration of WPH of neuronal impairment might result from the stimulation of neurogenesis.…”
Section: Wph Alleviates Hippocampal Impairments In Aici Ratsmentioning
confidence: 99%
“…Numerous pieces of evidence have revealed the stimulation by alcohol of the release of reactive oxygen species (ROS) and inflammatory cytokines in brain tissues, which certainly leads to oxidative stress and neuroinflammation. 6–9 As such, a more comprehensive understanding of the role of oxidative stress and neuroinflammation in mediating the development of AICI is urgently needed. Generally, the excessive accumulation of ROS is the initial response of brain tissue to chronic alcohol exposure and a subsequently enhanced release of inflammatory cytokines such as interleukin (IL)-6 and tumor necrosis factor (TNF)-α is observed.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol consumption can create a series of health problems in important organs in the body such as the liver (Axley et al, 2019) and the brain (Rao and Topiwala, 2020). A series of neurocognitive problems are known to manifest in individuals with AUD (Caballeria et al, 2020) that might persist even after long periods of abstinence. These impairments are related to structural and functional effects of alcohol in the brain.…”
Section: Introductionmentioning
confidence: 99%